THE GRAND HIGH WITCH’S CHARACTERIZATION IN ROALD DAHL’S THE WITCHES - Suwastini, Ni Komang Arie; Utami, Ida Ayu Made Istri; Paramita, Ni Wayan Nita (PRASI, 2024)
Roald Dahl’s children’s literature usually depicts children as the protagonist and the grown-ups as the antagonist. This study aims to describe The Grand High Witch’s character as the main antagonist in Roald Dahl’s The Witches (1983). This study employs interactive qualitative analysis by Miles, Huberman and Saldaña which has 3 simultaneous processes; data condensation, data display and conclusion drawing/verifying. These 3 processes are conducted simultaneously in an interactive process which means these processes will be carried repeatedly. In the novel, The Grand High Witch was portrayed as having a scary face which she covered with a mask in order to be beautiful and accepted in society. The Grand High Witch’s cruel and cunning natures were influenced by her hatred towards children. She was portrayed as an antagonist character because her hatred led her to do bad things. Then society will construct a mindset that people only can be a bad person or kind person. Whereas, people are born with multidimensional characters. Thus, these characters could provide insight to children that people in society come with various kinds of traits.